2020
DOI: 10.3389/fpls.2020.01192
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Overexpression of JERFs on Intracellular K+/Na+ Balance in Transgenic Poplar (Populus alba × P. berolinensis) Under Salt Stress

Abstract: Salt stress is one of the main factors that affect both growth and development of plants. Maintaining K + /Na + balance in the cytoplasm is important for metabolism as well as salt resistance in plants. In the present study, we monitored the growth (height and diameter) of transgenic Populus alba × P. berolinensis trees (ABJ01) carrying JERF36s gene (a tomato jasmonic/ethylene responsive factors gene) over 4 years, which showed faster growth and significant salt tolerance compared with non-transgenic poplar tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 101 publications
(198 reference statements)
0
5
0
Order By: Relevance
“…Interference with FDL expression enhanced the drought resistance of transgenic poplar (Yu et al, 2019). The K + /Na + homeostasis of root cells and tolerance to salt stress were improved in transgenic poplar overexpressing JERF36s (Ding et al, 2020). These studies provided insight into the mechanism of salt tolerance improvement in plants and will facilitate breeding strategies to improve salt tolerance.…”
Section: Resistance To Abiotic Stressmentioning
confidence: 86%
“…Interference with FDL expression enhanced the drought resistance of transgenic poplar (Yu et al, 2019). The K + /Na + homeostasis of root cells and tolerance to salt stress were improved in transgenic poplar overexpressing JERF36s (Ding et al, 2020). These studies provided insight into the mechanism of salt tolerance improvement in plants and will facilitate breeding strategies to improve salt tolerance.…”
Section: Resistance To Abiotic Stressmentioning
confidence: 86%
“…Whereas at Qiqihar, the DEGs from the ABJ01 vs. 9# comparison was mainly significantly enriched in Photosynthesis (28 DEGs), Oxidative phosphorylation (12 DEGs), and other pathways present in photosynthetic organisms. Studies have shown that overexpression of many ERF transcription factors, such as those found in poplar, soybean, tomato, wheat, and tobacco, result in stronger tolerance to abiotic and biotic stress by regulating the expression of stress-related genes ( Yao et al, 2016 ; Ku et al, 2018 ; Ding et al, 2020 ). This suggests that, compared with non-transgenic poplars, transgenic poplars mainly adapt to salt-alkali stress by regulating the expression of genes related to plant-pathogen interactions and photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that the AP2/ERF family of transcription factors, which are found mainly in plants, play very important roles in regulating diverse environmental stress responses, such as abiotic stresses (cold, heat, drought, salinity, and osmotic stress) and biotic stresses (herbivorous insects and microbial pathogens) ( Feng et al, 2020 ). AP2/ERF transcription factors, such as JERF36 and ERF76 have the ability to enhance salt tolerance in transgenic poplar by increasing ABA and GA biosynthesis ( Li et al, 2009 ; Yao et al, 2016 ; Ding et al, 2020 ). DREB transcription factor, for example, SALTRESPONSIVE ERF1 (SERF1), can amplify and transmit salt-inducing signals through the MAPK cascade signaling pathway, leading to a response to salt stress in the plant ( Schmidt et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations